Autophagy Is Indispensable for the Self-Renewal and Quiescence of Ovarian Cancer Spheroid Cells with Stem Cell-Like Properties. (17th September 2018) - Wang, Qian; Bu, Shixia; Xin, Dedong; Li, Boning; Wang, Lan; Lai, Dongmei
Abstract : Epithelial ovarian cancer has the highest mortality rate of all gynecologic cancers. Cancer stem cells are considered to be the initiating cells of tumors. It is known that spheroid culture promotes ovarian cancer cells to acquire stem cell characteristics and to become stem cell-like. But the mechanisms remain largely unclear. Our data show that autophagy is sustainably activated in ovarian cancer spheroid cells. Inhibition of autophagy by knockdown of ATG5 abolishes the self-renewal ability of ovarian cancer spheroid cells. Knockdown of ATG5 prevents ovarian cancer spheroid cells to enter quiescent state. Autophagy is critical for quiescent ovarian cancer spheroid cells to reenter the cell cycle because rapamycin can promote quiescent ovarian cancer spheroid cells to form colonies on soft agar and knockdown of ATG5 can arrest ovarian cancer cells in G0/G1. Autophagy and NRF2 form a positive feedback regulation loop to regulate reactive oxygen species (ROS) levels in ovarian cancer spheroid cells. The optimal ROS level, neither too high nor too low, facilitates the self-renewal marker, NOTCH1, to reach to the highest level. Bafilomycin A1 can impair the self-renewal of ovarian cancer spheroid cells by disturbing ROS levels.